A Bulk Planar SiGe Quantum-Well Based ZRAM with Low VT Variability - Dutta, S.; Mittal, S.; Lodha, S.; Ganguly, U.; Schulze, J. (2015 IEEE 7th International Memory Workshop, IMW 2015, 2015)
A planar bulk ZRAM is attractive from a simplicity, cost and scalability perspective - compared to SOI or FinFET based designs. Alternatively, the highly doped p-channel bulk planar ZRAM with electrostatic potential well- based hole-storage is susceptible to random- dopant-fluctuation (RDF) induced VT variability. Here, we propose and evaluate a planar bulk ZRAM device with an intrinsic channel of Si/SiGe/Si hetero-structure epitaxially grown on an n+Si well. TCAD simulations show excellent performance of 660mV VT shift at +/-1.5V operation and IREAD difference of 45A/m. In terms of RDF based VT variability, a VT of 12.8 mV is observed which is estimated to be a small fraction (∼51×) of the estimate VT shift (660mV) and 6.47× lower compared to p-doped channel based ZRAM. Initial experiments on MOSCAP devices validate the hole-storage in the SiGe well with a 0.5V VT shift and an excellent read disturb (>1000s).
CRIS-Team Scopus Importer:2021-06-29
Keywords: 1T DRAM; Bulk; planar; ZRAM